Variation in anti‐microbial prescription and complications post emergency appendicectomy in Australia: do we follow recommended guidelines?. Issue 3 (18th February 2019) - Thong, Da Wei; Kim, Jason; Dobson, Benjamin; Cheung, Henry; Arthur, Thomas; ,
Abstract : Background: This study aims to establish compliance levels to prescription guidelines among Australian surgeons in the use of antibiotics in the surgical management of appendicitis. The secondary outcomes are predictors of post‐operative infective complications; surgical site infection (SSI) and intra‐abdominal abscess (IAA) at 30 days. Methods: A multi‐centre, prospective, observational study was conducted over a period of 2 months with a 30‐day follow‐up. Patients were eligible for recruitment if they underwent appendicectomy for suspected appendicitis. Antibiotics prescription practices were recorded and compared to national guidelines. Results: A total of 1189 patients were recruited across 27 centres; 1081 (92.1%) patients were given prophylactic antibiotics at the time of appendicectomy. Patients with gangrenous appendicitis were more likely to receive prophylactic antibiotics (98.9%); lower rates of use were seen in the non‐appendicitis group (85.7%). A total of 619 (53.3%) patients received antibiotics in the post‐operative period. Despite recommendations, 300 (44.3%) patients with simple appendicitis received post‐operative antibiotics. Only six (2.9%) patients with complicated appendicitis did not receive antibiotics. Overall, SSI and IAA rates were 1.9% and 2.7%, respectively. Aboriginal and Torres Strait Islanders ( P  = 0.02) and patients with converted operations ( P  = 0.001) were more likely to have a SSI. Patients with complicated appendicitis and those operated on by a consultant were more likely to increase the odds of IAA (odds ratio 3.8 and 5.1, respectively). Conclusion: This broad‐based study shows mixed compliance with antibiotic guidelines in the surgical management of appendicitis in Australia. The use of post‐operative antibiotics in patients with simple appendicitis should be a target for antimicrobial stewardship programmes to prevent antibiotic over‐utilization. Abstract : Post‐operative infections and its relevance to use of antibiotics in surgical procedures are a highly debated topic and these factors and prescription habits have yet to be investigated in Australia. This study demonstrated that antibiotics tend to be given for simple and gangrenous appendicitis post‐operatively even though it was not indicated according to guidelines and a tendency for under‐prescribing of surgical prophylaxis antibiotics. This broad‐based study shows mixed compliance with antibiotic guidelines in the surgical management of appendicitis in Australia; targeted education programmes are recommended to address this issue to prevent the increasing surge of antibiotic‐resistant organisms.